The Single Sign On Model Using SAML and OAuth for Online Application of UPNYK - Akbar, Ahmad Taufiq; Prapcoyo, Hari; Perwira, Rifki Indra (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 4 (2024): JELIKU Volume 12 No 4, May 2024, 2024)
Keywords : Single Sign-On (SSO), Security Assertion Markup Language (SAML), authentication, OAuth (Open Athorization)